Wide band UV/Vis/NIR blazed-binary reflective gratings: two lithographic techniques investigation - Lee Mane-Si Laure (EDP Sciences, 2021)
We report on subwavelength reflective gratings for hyperspectral applications operating in the 340 nm-1040 nm spectral range. The blazed grating period is 30 μm and is composed of 2D subwavelength binary structures with sizes in-between 120 nm and 350 nm. We demonstrate the manufacturing of gratings on 3” wafers by two lithography technologies (e-beam or nanoimprint) followed by dry etching process. These subwavelength gratings enable broadband efficiency which is in average 15%-20% above the efficiency requirement for next generation of spectro-imagers for Earth observation missions and a wavefront error that is much smaller than the 100 nm requirement for space application.